Manajemen Pembelajaran Bahasa IndonesiaDi SMK Muhammadiyah Purwodadi - Sadiyo, Sadiyo; , Prof. Dr. Abdul Ngalim, M.M, M.Hum; , Dr. Sabar Narimo, M.M., M.Pd (2016)
The purpose of this research is 1) planning learning Indonesian in SMK Muhammadiyah Purwodadi 2) the implementation of learning Indonesian in SMK Muhammadiyah Purwodadi 3) evaluation of learning Indonesian in SMK Muhammadiyah Purwodadi. Data collection techniques using observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data in this study using triangulation. The results of this study were 1) The curriculum used in learning Indonesian in SMK Muhammadiyah Purwodadi use Unit Level Curriculum (SBC). Language learning plan outlined in Learning Implementation Plan (RPP) which is based on the syllabus. RPP compiled for each basic competency that can be implemented in one or more meetings. The availability of infrastructures as supporting the implementation of learning Indonesian is good enough. 2) Implementation of learning Indonesian is executed in accordance with RPP previously prepared by the teacher. Sebulum implementation of learning Indonesian at the start, teacher appreciation and review material covered previously, the learning step used is a) the initial activity, b) a core activity c) the final activity. The strategy used one of them is a learning model Directed Reading and Thinking Activity (DRTA) 3) Performance evaluation of learning Indonesian, held every turn of the Basic Competence of the results of the tests can determine the success of teaching and learning process that has been implemented before, how students can understand the material there is. The tests used to evaluate student learning outcomes in learning Indonesian mengguanakan written test in the form of objective test (multiple choice) and the essay. The purpose of the evaluation of learning Indonesian, among others, are: to determine the learning progress of students after participating in learning activities, determine the effectiveness of teaching methods applied by teachers and obtain input or feedback for teachers and students in order to improve teaching and learning activities that will take place. Keywords: Indonesian, management, vocational